Peran Kelompok Sadar Wisata (Pokdarwis) dalam Optimalisasi Wisata Edukasi Di Desa Galengdowo Kabupaten Jombang - Salmadina Putri Purnama Sari salmadina; Adinda Solinaputri Nurfadhila; Alief Faza Anugerah; Agung Budi Wicaksono; Putu Nandhika Pratama Artana; Kusuma Wardhani Mas’udah; Hasri Magfirotun Nisa (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The rapid development of the tourism sector has encouraged all regions to highlight the tourism potential in their respective regions. Likewise with Galengdowo Village which has tourism potential, as well as its existence in the world and the natural beauty and activities of its own citizens, gardening in salak gardens, and doing activities on earth which are used as educational tours. Tourism in Galengdowo Village has succeeded in inserting the concept of learning into its tour. Tourists who come not only take pictures and enjoy the natural beauty in the earth's area but can also learn how to milk cows and know the science and benefits of salak fruit. All educational tourism activities in Galengdowo Village cannot be separated from the role of the Tourism Awareness Group (POKDARWIS) which is the main driver of educational tourism managed by the local community itself.